2019
DOI: 10.1037/rep0000277
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of perceived personal and group discrimination against people with physical disabilities.

Abstract: To analyze the consequences for self-esteem of perceived discrimination against people with physical disabilities, as individuals and as a group. Method: A structural model based on the psychosocial literature was tested in a sample of 288 Spanish participants with different degrees of physical disability. This model predicted that personal perceived discrimination would be associated with the internalization of stigma that, in turn, would be negatively associated with the self-esteem of people with physical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
(83 reference statements)
1
22
0
2
Order By: Relevance
“…These results are in line with findings of studies with people with mental illness which showed that perceived discrimination was a predictor of internalized stigma (Brohan et al ., ). Similarly, in the sample of people with physical disabilities, personal perceived discrimination had positive direct effect on internalized stigma (Molero et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with findings of studies with people with mental illness which showed that perceived discrimination was a predictor of internalized stigma (Brohan et al ., ). Similarly, in the sample of people with physical disabilities, personal perceived discrimination had positive direct effect on internalized stigma (Molero et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized that participants with physical disabilities showed different levels of internalized stigma on each scale and that additional research is needed to examine internalized stigma among this group of people. Spanish study showed that internalized stigma had mediating effect between personal discrimination and self-esteem, as well as direct effect on self-esteem in people with physical disabilities (Molero et al, 2019). Taft, Ballou and Keefer's (2013) study conducted with people with inflammatory bowel disease goes along with findings that internalized stigma has a negative effect.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Stigma scale for chronic illness 9-item version (SSCI-9). The Spanish adaptation of the internalized stigma subscale of the SSCI [92], which had shown adequate psychometric properties in a of people with different disabilities, was used for the research [93,94]. Example items are "Because of my illness, I feel emotionally distant from other people" and "Because of my illness, I feel embarrassed in social situations".…”
Section: Methodsmentioning
confidence: 99%
“…In Nigeria, the existence of widespread discrimination against PWDs in terms of job access and security has been identified [ 36 ]. In Spain, personal and group discrimination has been shown to harm self-esteem of PWDs in various ways [ 37 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%